Exploring the role of Microbiome in Susceptibility, Treatment Response and Outcome among Tuberculosis Patients from Pakistan: study protocol for a prospective cohort study (Micro-STOP) - Zia Ul-Haq; Muhammad Shahzad; Simon C Andrews (BMJ Open)
Introduction Tuberculosis (TB) caused by Mycobacterium tuberculosis is a common infectious disease associated with significant morbidity and mortality, especially in low-income and middle-income countries. Successful treatment of the disease requires prolonged intake (6–8 months) of multiple antibiotics with potentially detrimental consequences on the composition and functional potential of the human microbiome. The protocol described in the current study aims to identify microbiome (oral and gut) signatures associated with TB pathogenesis, treatment response and outcome in humans.Methods and analysis Four hundred and fifty, newly diagnosed patients with TB from three district levels (Peshawar, Mardan and Swat) TB diagnosis and treatment centres, will be recruited in this non-interventional, prospective cohort study and will be followed and monitored until treatment completion. Demographic and dietary intake data, anthropometric measurement and blood, stool and salivary rinse samples will be collected at baseline, day 15, month-2 and end of the treatment. Additionally, we will recruit age (±3 years) and sex-matched healthy controls (n=30). Blood sampling will allow monitoring of the immune response during the treatment, while salivary rinse and faecal samples will allow monitoring of dynamic changes in oral and gut microbiome diversity. Within this prospective cohort study, a nested case–control study design will be conducted to assess perturbations in oral and gut microbiome diversity (microbial dysbiosis) and immune response and compare between the patients groups (treatment success vs failure).Ethics and dissemination The study has received ethics approval from the Ethic Board of Khyber Medical University Peshawar, and administrative approval from Provincial TB Control Programme of Khyber Pakhtunkhwa, Pakistan. The study results will be presented in national and international conferences and published in peer-reviewed journals.Trial registration number NCT04985994.